Continuum in the X‐Z‐‐‐Y weak bonds: Z= main group elements. Issue 2 (17th August 2015) - Joy, Jyothish; Jose, Anex; Jemmis, Eluvathingal D.
Abstract : The Continuum in the variation of the X‐Z bond length change from blue‐shifting to red‐shifting through zero‐ shifting in the X‐Z‐‐‐Y complex is inevitable. This has been analyzed by ab‐initio molecular orbital calculations using Z= Hydrogen, Halogens, Chalcogens, and Pnicogens as prototypical examples. Our analysis revealed that, the competition between negative hyperconjugation within the donor (X‐Z) molecule and Charge Transfer (CT) from the acceptor (Y) molecule is the primary reason for the X‐Z bond length change. Here, we report that, the proper tuning of X‐ and Y‐group for a particular Z‐ can change the blue‐shifting nature of X‐Z bond to zero‐shifting and further to red‐shifting. This observation led to the proposal of a continuum in the variation of the X‐Z bond length during the formation of X‐Z‐‐‐Y complex. The varying number of orbitals and electrons available around the Z‐atom differentiates various classes of weak interactions and leads to interactions dramatically different from the H‐Bond. Our explanations based on the model of anti‐bonding orbitals can be transferred from one class of weak interactions to another. We further take the idea of continuum to the nature of chemical bonding in general. © 2015 Wiley Periodicals, Inc. Abstract : Red‐ and blue‐ shift in the X‐Z bonds during the X‐Z‐‐‐Y complex formation has been analyzed. A continuum in the X‐Z bond length is observed for various classes of weak bonds such as H‐bonds, halogen‐bonds, chalcogen‐bonds, and pnicogen‐bonds. The balance between negative hyperconjugation within the X‐Z molecule and charge transfer from Y‐group provides a working model to explain the observations. The definition of the continuum in the weak (X‐Z‐‐‐Y) interactions is profitably extended to include strong (Z‐Y) chemical bonds as well.